2018
DOI: 10.1007/s10753-018-0838-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Enhances Wnt Signal by Inhibiting DKK1

Abstract: Aberrant endochondral bone formation in the physis is a unique bone lesion in neonatal-onset multisystem inflammatory disease (NOMID), also called chronic infantile neurologic cutaneous articular (CINCA), the most severe of the cryopyrin-associated periodic syndrome (CAPS) diseases, which are interleukin-1β (IL-1β)-related monogenic autoinflammatory diseases. The wingless (Wnt) pathway plays an important role in osteoblast differentiation. In this study, we explored the potential role of IL-1β on the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…shows downregulation of SOST and DKK-1. This is in line with another publication in fibroblast-like synoviocytes (Yoshida et al, 2018). Thus, pro-inflammatory molecules might have potential to enhance as well as to downregulate Sost and Dkk-1, depending on the cell type.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…shows downregulation of SOST and DKK-1. This is in line with another publication in fibroblast-like synoviocytes (Yoshida et al, 2018). Thus, pro-inflammatory molecules might have potential to enhance as well as to downregulate Sost and Dkk-1, depending on the cell type.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the current knowledge, Sost is also considered an interesting target for therapy in endodontics. Dkk-1 is a contributor to dentin formation and mineralization (Han et al, 2011), it might play a role in root resorption (Zhu et al, 2013) and it is possibly connected to the inflammatory response and bone resorption in periapical lesions (Zhang et al, 2014). Hence, also Dkk-1 could be of interest as target in regenerative endodontic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The difference could be explained in part by the short‐term cytokine data which not only demonstrated elevated levels of IL‐1β produced by AD‐MSC cultures but also higher concentrations of PGE 2 . IL‐1β promotes canonical wnt signaling which is a central intracellular signaling pathway involved in osteogenesis . Moreover, PGE 2 has been shown to be a key cytokine necessary for promoting bone healing and regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β promotes canonical wnt signaling which is a central intracellular signaling pathway involved in osteogenesis. 38 Moreover, PGE 2 has been shown to be a key cytokine necessary for promoting bone healing and regeneration. 39,40 However, to further confirm this hypothesis cytokine analysis on the inflammatory differentiation media at early and late time-points are warranted and intracellular signaling pathway inhibition experiments should be performed.…”
mentioning
confidence: 99%
“…Several studies have reported that is a positive regulator of Wnt signaling pathway [11][12][13]. We then hypothesized that CAF-derived may exert its function through regulating Wnt signaling pathway in bladder cancer.…”
Section: Methodsmentioning
confidence: 99%